Gamification as a Social Phenomenon and Gamification Heuristics Criteria from Social Sciences Perspective - Bilge Aksay; Samet Oran; Muhammet Aktaş; Esen Yildirim; Fatih Kiliç (Plural: History, Culture, Society)
The widespread adoption of gamification across various domains necessitates robust methodologies to gauge its impact and efficacy. This study delves into heuristic evaluation techniques utilized in a European Union project where partners assessed gamification applications focused on cultural heritage in their respective countries. Notably, this study assesses gamification as a social phenomenon and evaluates gamification assessment criteria in practice for five gamification implementations that reflect Türkiye’s cultural heritage. Recognising gamification as a social phenomenon, this research evaluates seven key dimensions: collective participation, cultural integration, social interaction, motivational dynamics, technological mediation, dynamic evolution, and observability/measurability. Assessment criteria, categorised into intrinsic, extrinsic, and context-dependent motivational heuristics, are analysed through the lens of prominent social science theories, including Self-Determination Theory, Expectancy Theory, and Goal-Setting Theory, alongside learning paradigms such as Constructivist and Experiential Learning. The findings illuminate how gamification influences user engagement and learning, offering significant implications for designing more effective gamification strategies. This comprehensive analysis underscores the potential of integrating robust social science theories and evaluating it as a social phenomenon to enhance the theoretical and practical understanding of gamification’s role in modern societal contexts.